THE PLAYFUL AND THE HOSPITALIZED CHILD - Quitéria Fernandes Ferreira, Ana; Barros de Valmoré Fernandes, Marcelo; Lobato de Souza Costa, Debora; da Silva Carvalho, Denise; Cristina Faustino do Rego, Elen; Rodrigues da Silva, Natália; Aparecida Tavares Fialho Bezerra, Maria; Dayanna Alves Resende, Tamires; Porfirio Carvalho, Larissa (Health and Society, 2023)
This study is reflective, gathering literature on the topic of playfulness for children in the hospital context. It was evident that the bond between children and health professionals with the establishment of conversation, grants greater understanding of the need for that moment experienced by the child and of all activities developed in that space, favoring greater acceptability and flexibility in their handling, reflecting on clinical improvement. surviving the shortest hospitalization time by achieving the expected results.